A Randomized, Controlled Trial of Poractant Alfa versus Beractant in the Treatment of Preterm Infants with Respiratory Distress Syndrome - Dizdar, Evrim Alyamac; Sari, Fatma Nur; Aydemir, Cumhur; Oguz, Serife Suna; Erdeve, Omer; Uras, Nurdan; Dilmen, Ugur (American Journal of Perinatology, 2012)
We prospectively evaluated the differences in clinical responses and short-term outcomes in preterm infants with respiratory distress syndrome (RDS) treated with poractant alfa or beractant. Premature infants with RDS were randomized to poractant alfa or beractant treatment between July 2008 and June 2009. Patients were followed until 40 weeks of corrected gestational age or death. The fraction of inspired oxygen (Fio2) after surfactant treatment, need for repeat doses, and duration of respiratory support and hospitalization were evaluated between groups. Sixty-one infants received poractant alfa and 65 received beractant. Significantly more patients in the beractant group required ≥2 doses of surfactant compared with the poractant alfa group (31% versus 12%, p = 0.023). Extubation rate within the first 3 days after surfactant administration was higher in the poractant alfa group than in the beractant group (81% versus 55.9%, p = 0.004). Posttreatment Fio2 requirement in the poractant alfa group was significantly lower than in the beractant group on days 1, 3, and 5. Overall mortality and morbidities were similar between groups. Survival free of bronchopulmonary dysplasia (BPD) at the end of study period was 78.7% and 58.5% in poractant alfa and beractant groups, respectively (p = 0.015). Our study confirms the rapid onset of action, less need for redosing, rapid extubation, and higher survival free of BPD in preterm infants treated with poractant alfa.
Keywords: beractant; poractant alfa; preterm; respiratory distress syndrome; surfactant